Current Approaches to Planning and Conducting Clinical Trials of Medicinal Products for the Treatment of Crohn's Disease - А. N. Bogdanov; E. V. Gorbunova; D. V. Goryachev; E. V. Petraneva (Регуляторные исследования и экспертиза лекарственных средств, 2020)
Accumulation of knowledge on Crohn’s disease, and development of biological products intended for the treatment of its underlying cause formed the basis for the development of objective methods for assessing the intensity of the pathological process, which in turn affected scientific approaches to the planning of clinical trials in this field. To date, many international recommendations related to planning, conduct of clinical trials, and analysis of their results, have been updated. Considerable experience has been gained with clinical trials of medicines intended for the treatment of Crohn’s disease. Therefore, the methodological approach to the planning of pivotal clinical studies needs to be reviewed. The aim of the study was to develop requirements for planning and expert evaluation of clinical trials conducted with the aim of obtaining marketing authorisation for medicinal products for the treatment of Crohn’s disease. The paper analyses regulations, recommendations, and scientific literature on the treatment of Crohn’s disease and describes the methodology for planning clinical trials. It describes the evolution of approaches to clinical research planning since biological medicines appeared. The authors substantiate the need for an integrated concept of clinical research, which covers goals, estimated therapeutic effect, design, and choice of the statistical analysis method. They also provide scientific arguments in favour of a combined primary endpoint including endoscopic remission and the assessment of treatment results by the patient. The paper lists patient eligibility criteria in terms of “inducing and/or maintaining remission of the disease”. The authors analyse the main intercurrent events, their influence on the therapeutic effect, and propose approaches to the planning of endpoints, including assessment of intercurrent events. The paper highlights the fact that the principles of planning and conducting Phase III clinical trials need to be consistent with the evidence-based strategies of reducing the risk of incorrect assessment of efficacy and safety of new medicines, and that the obtained results have to meet the requirements of the regulatory authorities at the stage of marketing authorisation.